Breeding in the Economically Important Brown Alga Undaria pinnatifida: A Concise Review and Future Prospects - Shan, Tifeng; Pang, Shaojun (Frontiers in Genetics, 2021)
Undaria pinnatifida is the commercially second most important brown alga in the world. Its global annual yield has been more than two million tonnes since 2012. It is extensively cultivated in East Asia, mainly consumed as food but also used as feed for aquacultural animals and raw materials for extraction of chemicals applicable in pharmaceutics and cosmetics. Cultivar breeding, which is conducted on the basis of characteristics of the life history, plays a pivotal role in seaweed farming industry. The common basic life history shared by kelps determines that their cultivar breeding strategies are similar. Cultivar breeding and cultivation methods of U. pinnatifida have usually been learned or directly transferred from those of Saccharina japonica. However, recent studies have revealed certain peculiarity in the life history of U. pinnatifida. In this article, we review the studies relevant to cultivar breeding in this alga, including the peculiar component of the life history, and the genetics, transcriptomics and genomics tools available, as well as the main cultivar breeding methods. Then we discuss the prospects of cultivar breeding based on our understanding of this kelp and what we can learn from the model brown alga and land crops.